Wing pattern variation and DNA barcodes defy taxonomic splitting in the New Zealand Pimelea Looper Notoreas perornata (Walker) (Lepidoptera: Geometridae: Larentiinae): the importance of populations as conservation units - Hoare, Robert J.b.; Patrick, Brian H.; Buckley, Thomas R.; Brav-Cubitt, Talia (Zootaxa, 2023)
The endemic Notoreas perornata (Walker, 1863) complex (Lepidoptera: Geometridae: Larentiinae) from the North Island and northern South Island of New Zealand is reviewed. Larvae feed on Pimelea spp. (Thymelaeaceae), frequently in highly fragmented and threatened shrubland habitats. Allopatric populations tend to differ in size and wing pattern characteristics, but not in genitalia; moreover extensive variation renders recognition of subspecies / allopatric species based on any species concept problematic. A mitochondrial DNA gene tree is not congruent with morphology and indicates rapid recent divergence that has not ‘settled’ into diagnosable lineages. Based on our results, we synonymise Notoreas simplex Hudson, 1898 with N. perornata (Walker, 1863), and retain N. perornata as a single, highly diverse but monotypic species. All known populations are illustrated to display variation. For conservation purposes, we recommend the continued recognition within the species of 10 populations or groups of populations that appear to be on the way to diverging at subspecific level based on morphological and/or DNA data. The conservation status of all these populations is reviewed. One conservation unit, comprising the populations from Westland, has not been seen since 1998 and is feared possibly extinct.